2004
DOI: 10.1038/sj.cdd.4401519
|View full text |Cite
|
Sign up to set email alerts
|

Perp is required for tissue-specific cell survival during zebrafish development

Abstract: The tumor suppressor p53 has two alternative effects, causing either cell cycle arrest or apoptosis. These different effects are supposed to be mediated by the transcriptional activation of different target genes. perp, encoding a transmembrane protein of the Pmp22 family, is a transcriptional p53 target exclusively upregulated in apoptotic cells. However, its role during normal development had remained largely unclear. Here, we report the isolation and characterization of a zebrafish perp homolog. Upon overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 76 publications
2
35
0
Order By: Relevance
“…First strand cDNA synthesis was performed on 2 mg of total RNA using oligo dT primer and Superscript III reverse transcriptase (Invitrogen). Quantitative real time RT-PCR (QRT-PCR) was performed with the SYBR green PCR kit (Applied Biosystems) in a DNA Engine Opticon-Continuous Fluorescence Detection system (MJ Research), using the following primer sets: elongation factor 1a (ef1a) 37 (control): sense, TCA CCC TGG GAG TGA AAC AGC; antisense, ACT TGC AGG CGA TGT CAG CAG; p53: 38 sense, GCG ATG AGG AGA TCT TTA CCC; antisense, ACA AAG GTC CCA GTG GAG TG; p21: 39,40 sense, AGC TGC ATT CGT CTC GTA GC; antisense, TGA GAA CTT ACT GGC AGC TTC A; bax: 39,40 sense, GCA GTG GCA ATG ACC AGA TA; antisense, GGA AAA CTC CGA CTG TCT GC. All samples were quantified by the comparative cycle threshold (Ct) method for relative quantification of gene expression, normalized to ef1a.…”
Section: Rna Extraction and Quantitative Real Time Rt-pcr Analysismentioning
confidence: 99%
“…First strand cDNA synthesis was performed on 2 mg of total RNA using oligo dT primer and Superscript III reverse transcriptase (Invitrogen). Quantitative real time RT-PCR (QRT-PCR) was performed with the SYBR green PCR kit (Applied Biosystems) in a DNA Engine Opticon-Continuous Fluorescence Detection system (MJ Research), using the following primer sets: elongation factor 1a (ef1a) 37 (control): sense, TCA CCC TGG GAG TGA AAC AGC; antisense, ACT TGC AGG CGA TGT CAG CAG; p53: 38 sense, GCG ATG AGG AGA TCT TTA CCC; antisense, ACA AAG GTC CCA GTG GAG TG; p21: 39,40 sense, AGC TGC ATT CGT CTC GTA GC; antisense, TGA GAA CTT ACT GGC AGC TTC A; bax: 39,40 sense, GCA GTG GCA ATG ACC AGA TA; antisense, GGA AAA CTC CGA CTG TCT GC. All samples were quantified by the comparative cycle threshold (Ct) method for relative quantification of gene expression, normalized to ef1a.…”
Section: Rna Extraction and Quantitative Real Time Rt-pcr Analysismentioning
confidence: 99%
“…p53 heterozygous mice exhibited the expected increased mortality in comparison to wild-type mice, with a median survival time of 18 months, consistent with previous findings. 6 Upon aging the wild-type and Perp heterozygous mouse cohorts, no statistically significant difference in survival was observed: both genotypes displayed a median survival time of 28.5 months, with a similar incidence of tumor development in both groups (Figure 1a). In total, 80% of the mice of each genotype developed at least one benign or malignant tumor before death, and 21% of each cohort developed multiple tumors.…”
mentioning
confidence: 97%
“…Consistent with a dual role for Perp, experiments in zebrafish have shown that Perp participates in both UV-induced, p53-dependent apoptosis and proper development of the skin and pectoral fins. 6 In both of these model organisms, loss of Perp has significant deleterious effects in the developing animal, but the more long-term effects of this absence have yet to be determined.…”
mentioning
confidence: 99%
“…20 In order to discount this as the cause for the apoptosis seen when injecting with zNEDD1 MOs, co-injections were carried out with a previously characterised p53 MO. 20,21 After co-injection of zNEDD1 MOs with the p53 MO, apoptosis was still occurring, although the number of TUNEL-positive cells appeared to be slightly lower in the co-injected embryos (56 ± 5 TUNEL-positive cells per embryo, Figure 4e and f and Supplementary Figure S5). As this phenotype was rescued by co-injection with zNEDD1 mRNA, this suggests that some of the apoptosis in embryos depleted of zNEDD1 by MO injection relies on p53 activity.…”
Section: Resultsmentioning
confidence: 99%